(untitled) (Islas, 2025)
Introduction: This research proposes a discourse analysis guide for journalistic texts focused on the three dimensions of discourse —syntax, semantics, and pragmatics— to facilitate the understanding of the different levels of journalistic texts in relation to their communicative and socio-historical context. Methods: The use of the bibliographic-documentary method enabled the theoretical foundation and the definition of the research categories. The theoretical framework, along with expert consultation, addressed the empirical dispersion surrounding the development of this adapted technique for discourse studies. Results: The main outcome of the research was the development of a discourse analysis guide for journalistic texts, focused on the three dimensions of discourse and aligned with the analytical standards of media discourse and communication in general. Conclusions: The proper description of the formal macrostructures of media discourse within its production context contributes to a better understanding of the factors underlying the mental representations of events that give rise to discursive production—key elements in the study of press discourse.